2018
DOI: 10.1177/0890334418768792
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Healthy Eating and Exercise Behaviors Among Low-Income Breastfeeding Mothers

Abstract: Low-income breastfeeding mothers may be more receptive to nutrition education or interventions that focus on the mother-infant dyad rather than solely on maternal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
1
9
0
1
Order By: Relevance
“…The higher FV intake may be explained by maternal beliefs about the importance of a healthy diet. In focus group discussions with low-income women who chose to breastfeed, respondents saw a connection between maternal diet and infant health and were motivated to eat healthfully to benefit the child [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher FV intake may be explained by maternal beliefs about the importance of a healthy diet. In focus group discussions with low-income women who chose to breastfeed, respondents saw a connection between maternal diet and infant health and were motivated to eat healthfully to benefit the child [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to confirm these findings and to identify other demographic and psychosocial determinants of VM scores. Warranting examination are psychosocial variables consistently shown to influence adult FV intake as measured by self-report, e.g., FV access, availability, and taste preferences [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ,…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this could be explained by the fact that 87.7% of respondents think that the best approach against obesity is via nutrition as opposed to 51.7% who think surgery is the better option (Macmillan and Olson 2019). [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have been conducted to explore the health behaviors of breastfeeding women [ 9 , 10 ]. A mixed methods study found women ( n = 6) to be motivated for exercise by stress relief and energy improvement however women were concerned that exercise negatively influenced milk supply [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study was limited by its small sample size and questions were only focused on exercise. Another study determined low-income mothers were motivated to engage in healthy behaviors like physical activity and healthy eating if it benefited their child, but they were not seeking out information regarding how to do so [ 10 ]. While this study is a crucial first step in this important work, it is limited by focusing only on low-income women and women were not required to be breastfeeding at the time of study participation, thus the results may have been based on recall experiences.…”
Section: Introductionmentioning
confidence: 99%